Plasmonic enhancement of photocurrent in MoS2 field-effect-transistor - Lin, Jiadan (2013)
The two-dimensional material, molybdenum disulfide (MoS2), has attracted considerable attention for numerous applications in optoelectronics. Here, we demonstrate a plasmonic enhancement of photocurrent in MoS2 field-effect-transistor decorated with gold nanoparticles, with significantly enhanced photocurrent peaked at the plasmon resonant wavelength around 540 nm. Our findings offer a possibility to realize wavelength selectable photodetection in MoS2 based phototransistors.